Guaiane‐type Sesquiterpenoid Dimers from Artemisia zhongdianensis and Antihepatoma Carcinoma Activity via the p38MAPK Pathway - Dong, Wei; Ma, Wen‐Jing; Ma, Yun‐Bao; Li, Feng‐Jiao; Li, Tian‐Ze; Wang, Yong‐Cui; He, Xiao‐Feng; Geng, Chang‐An; Zhang, Xue‐Mei; Chen, Ji‐Jun (Chinese journal of chemistry, 2023)
Comprehensive Summary 17 new guaiane‐type sesquiterpenoid dimers (GSDs), artemzhongdianolides B1—B17 (1—17), were isolated from Artemisia zhongdianensis under the guidance of bioassay, and elucidated by spectral analyses (HRESIMS, 1D and 2D NMR, IR, ECD). The absolute configuration of compounds 1, 3, 7, 9, 10, and 13 was determined by single‐crystal X‐ray diffraction analyses. Structurally, artemzhongdianolides B1 (1) and B2 (2) were the first example of the GSDs fused via a C‐13/C‐13' single bond, and artemzhongdianolides B3—B17 were [4 + 2] Diels–Alder adducts of two monomeric guaianolides. Most of the compounds showed antihepatoma cytotoxicity with IC50 values ranging from 9.9 to 170.1 μmol/L. Importantly, artemzhongdianolide B9 (9) was the most active one against three hepatoma cell lines with IC50 values of 13.1 μmol/L (HepG2), 19.5 μmol/L (Huh7), and 19.5 μmol/L (SK‐Hep‐1), and dose‐dependently inhibited cell migration and invasion, induced G1 cell cycle arrest and cell apoptosis in HepG2 cells. Compound 9 might suppress HepG2 cells via affecting the p38MAPK signaling pathway suggested by machine learning approach, and significantly upregulated expression of phosphorylated p38 validated by Western blot assay. 17 new guaiane‐type sesquiterpenoid dimers (GSDs), artemzhongdianolides B1—B17 (1—17), were isolated from Artemisia zhongdianensis. Compound 9 was the most active one against three hepatoma cell lines, and dose‐dependently inhibited cell migration and invasion, induced G1 cell cycle arrest and cell apoptosis in HepG2 cells. Compound 9 might suppress HepG2 cells via affecting the p38MAPK signaling pathway suggested by machine learning approach, and significantly upregulated expression of phosphorylated p38 validated by Western blot assay.